Intracranial Hemorrhage in a Pregnant Patient with COVID-19: A Case Report - Metin Şentürk; Mustafa Cihangiroğlu (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2021)
Pregnancy reportedly increased the risk of intracranial hemorrhage (ICH), and Coronavirus disease-2019 (COVID-19) has been found to be an associated factor. We report the case of a 26-year-old pregnant woman who was admitted to our hospital with a chief complaint of fatigue; she was diagnosed with COVID-19 and later developed ICH after cesarean section (C/S) delivery. The patient was tested for COVID-19 as her husband tested positive for it. After COVID-19 diagnosis, labor induction was decided due to amniorrhexis. Despite eight hours of labor induction, owing to the asynclitic presentation of the fetus, vaginal delivery did not progress; therefore, a C/S was performed. The patient gave birth to a healthy baby, and favipiravir treatment was initiated. On day nine of hospitalization, she complained of nausea and headache. Brain computed tomography revealed an intraparenchymal hematoma. The patient did not have any risk factors, except pregnancy. The hematoma was removed, and hemorrhage was resolved; however, a brain edema developed. After dexamethasone and mannitol treatment, her condition improved and she was transferred to the clinic. In conclusion, ICH can be observed in the postpartum period in a pregnant patient with COVID-19 with no risk factors other than pregnancy.